Tecnologia e política: o voto e seu suporte - Rivero, Facundo Guerra (2012)
This study aims to study the vote in different historical periods of Brazilian society, with greater emphasis on its current configuration, the electronic voting, and understand how it relates to a society that Gilles Deleuze called the control society, according to the corollary that maintains this social configuration standing: trust, participation and security, as well as study the relationship between the mechanism of the vote and the possibilities of controlling a population, its relations with representative democracy, the vote as a vector diagram of control or power device